Nutrient release by a Brazilian sedimentary zeolite - Marisa B.M. Monte; Antonieta Middea; Paulo R.P. Paiva; Alberto C.C. Bernardi; Nélio G.A.M. Rezende; Milton Baptista-Filho; Marcelo G. Silva; Helion Vargas; Helio S. Amorim; Fernando de Souza-Barros (Anais da Academia Brasileira de Ciências, 2009)
This report describes the characterization of a sedimentary occurrence from the Parnaíba Basin, Brazil, containing the zeolite stilbite intertwined with smectitic clay mineral. The head samples from different sites present a wide content range of the zeolitic phase - 15% to 50%. The use of simple separation techniques - conventional gravitic treatments - yields concentrates containing about 67% of the zeolitic component. Assays with the amendments of these concentrates with plant nutrients yield release rates matching those reported for similar commercial products. São apresentadas as propriedades físico-químicas de uma ocorrência sedimentar da Bacia do Parnaíba, Brasil, da zeólita estilbita, agregada a uma argila esmectítica. As amostras de diferentes sítios apresentam uma ampla variação do mineral zeolítico: entre 15% a 50%. A utilização de espirais concentradoras foi suficiente para obtenção de concentrados contendo até 67% do mineral. Ensaios laboratoriais do concentrado dopado com fertilizantes revelam taxas de liberação de nutrientes comparáveis aos obtidos com produtos comerciais similares.